Understanding the Role of Adenosine Receptors in the Myofibroblast Transformation in Peyronie's Disease. Issue 7 (8th June 2018) - Mateus, Marta; Ilg, Marcus M.; Stebbeds, William J.; Christopher, Nim; Muneer, Asif; Ralph, David J.; Cellek, Selim
Abstract: Background: Peyronie's disease (PD) is a chronic fibrotic disease of the penis affecting a significant number of men worldwide without effective medical treatments. Myofibroblasts are pivotal in the pathogenesis of PD. Adenosine and adenosine receptors have been suggested to be involved in the pathophysiology of fibrosis. Aim: To understand the role of adenosine receptors in myofibroblast transformation in PD. Methods: Fibroblasts were isolated from the non-PD tunica albuginea (TA) tissue and PD plaque tissue and were transformed into myofibroblasts using transforming growth factor (TGF)-β1. Quantification of α-smooth muscle actin and adenosine receptors (adenosine receptor A1 [ADORA1], adenosine receptor A2A, adenosine receptor A2B [ADORA2B], and adenosine receptor A3) was performed using immuno-cytochemistry, in-cell enzyme-linked immuno-sorbent assay (ICE), and real-time reverse transcription quantitative polymerase chain reaction. The effect of various adenosine receptor agonists or antagonists on TGF-β1-induced myofibroblast transformation was measured using ICE. Outcomes: Expression of adenosine receptors in myofibroblasts obtained from human TA and the effect of adenosine receptor ligands on myofibroblast transformation were investigated. Results: The experiments showed that the protein and messenger RNA levels of α-smooth muscle actin in non-PD TA cells and PD plaque-derived cells were significantly higher in cells exposed to TGF-β1 than those not treated with TGF-β1. 2 of 4 adenosine receptors (ADORA1 and ADORA2B) were found to be expressed in both cell populations. Among various adenosine receptor agonists/antagonist investigated, only ADORA2B agonist, BAY 60-6583, significantly inhibited myofibroblast transformation in a concentration-dependent manner when applied simultaneously with TGF-β1 (IC50 = 30 μmol/L). Clinical Translation: ADORA2B agonists may be clinically efficacious in early-stage PD. Strengths & Limitations: The strength of this study is the use of primary fibroblasts from human TA. Limitation of the study is the high concentrations of the ligands used. Conclusion: The effect of an ADORA2B agonist on TGF-β1-induced myofibroblast transformation shows a novel potential therapeutic target for PD if applied during early, non-stable phase of PD.